THE POTENTIAL OF LOCAL WISDOM AS A PILLAR OF SHARIA-BASED ECONOMY IN JAMBI PROVINCE - Yuliana, Yuliana; Aditiawarman, Andika; Tauvani, A. Yuli; dewi, Novriana; Salmia, Salmia (ILTIZAM Journal of Shariah Economics Research, 2025)
This study aims to explore the potential of local wisdom in Jambi Province in supporting the development of a sharia-based economy. Employing a qualitative-descriptive approach and field data, the research finds that local values such as gotong royong (mutual cooperation), musyawarah (deliberation), and traditional trading ethics embody principles aligned with Islamic economic teachings. These cultural values not only reflect social norms but also serve as a foundation for an ethical and sustainable economic system. Therefore, integrating local wisdom into sharia economic policy is essential for the contextual success of the Islamic economic framework.